Policing and Islamophobia in Germany: The Role of Workplace Experience - Mescher, Heidi (International Journal of Conflict and Violence (IJCV), 2008)
This study starts from a recognition that the German police have a significant potential to promote integration in contemporary multiethnic Germany. It employs three measures of Islamophobic attitudes and contact quality amongst a sample of 727 German police officers, and relates these to measures of job satisfaction, political affiliation, individual responsibility, and recognition. The data reveal Islamophobia to be significantly linked to these variables. Detailed analyses indicate that the respondents’ experience of policing may produce levels of dissatisfaction that impacts upon their outgroup attitudes. The implications of this for initiatives to promote police-Muslim relations are explored.